Saint Kitts and Nevis. Significant achievements 2013 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Saint Kitts and Nevis during 2013 are identified, with respect to the needs and interests of the country, strengthening issues such as leadership, financing, agrotourism, innovation, food safety, zoology, food safety, manipulation of food, costs, organic production, youth and use of shade houses.